2017
DOI: 10.1111/jvs.12509
|View full text |Cite
|
Sign up to set email alerts
|

Complex plant community responses to modifications of disturbance and nutrient availability in productive permanent grasslands

Abstract: Question Do the effects of grazing and fertilization on taxonomic and functional diversity follow the dynamic equilibrium model? Location Long‐term permanent upland grasslands, Massif‐central, France. Methods Over 8 yr, we monitored vegetation changes in 24 experimental plots in two productive grasslands after modification of grazing intensity (including abandonment) or fertilization regime (including cessation of fertilization). Botanical surveys and plant trait measurements (LDMC, SLA and reproductive plant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 36 publications
3
14
0
Order By: Relevance
“…However, mountain grasslands are often used as grazing grounds for livestock, with intensity varying in relation to elevation. In previous studies, added fertilisation and mowing has led to observed trait convergence and divergence depending on the attribute examined and the type/intensity of treatment (Bloor & Pottier, 2014;Louault et al, 2017;Mason et al, 2011).…”
Section: Variations Of Assembly Processes Along Environmental Gradimentioning
confidence: 97%
“…However, mountain grasslands are often used as grazing grounds for livestock, with intensity varying in relation to elevation. In previous studies, added fertilisation and mowing has led to observed trait convergence and divergence depending on the attribute examined and the type/intensity of treatment (Bloor & Pottier, 2014;Louault et al, 2017;Mason et al, 2011).…”
Section: Variations Of Assembly Processes Along Environmental Gradimentioning
confidence: 97%
“…; Louault et al . ). Nonetheless, the extraordinary growth of available data has left many empirical patterns of trait variation unexplained (Moles ).…”
Section: Introductionmentioning
confidence: 97%
“…During the last two decades several theoretical frameworks were developed for improving the theoretical basis of trait-based ecology (Westoby et al 2002;Grime 2006;Enquist et al 2007;Shipley 2010). Following the historical development of classical plant ecology (Whittaker 1967;Austin & Austin 1980), much research in this field has focused on the response of plant traits, particularly CWM and CWV, to soil resource gradients (Pakeman et al 2008;Cornwell & Ackerly 2009;Laliberte et al 2012;Louault et al 2017). Nonetheless, the extraordinary growth of available data has left many empirical patterns of trait variation unexplained (Moles 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Ten years of contrasted management had strongly modified the functional diversity and aboveground production of this fertile upland grassland (Herfurth et al 2015;Louault et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The local climate is semi-continental with oceanic influences (mean annual temperature 8.5 °C, mean annual precipitation 784 mm, Table 1). The site supports mesotrophic multi-specific permanent grassland, dominated by species with high Ellenberg indicator values for N (Schaffers and Sykora 2000), indicating a high level of fertility for the site (Table S1; Louault et al 2017). The soil is a cambisol with a sandy loam texture, developed on granitic bedrock.…”
Section: Methodsmentioning
confidence: 99%